PERSEPSI TAMPILAN PEWARNAAN HIDANGAN AKIBAT TEMPERATUR WARNA CAHAYA DAN DAMPAKNYA PADA SELERA BERSANTAP DI CAFE - Leonardo; Chandrahera, Yuma; Suhanjoyo, Shirly N. (Universitas Ciputra Surabaya, 2024)
Correlated Color Temperature/CCT from artificial lighting in casual dining area at cafés is used to guide visitors visual perception through the interior atmosphere and dish display when served. Its visual impact triggers a non-visual response in the form of the visitors perception to rise appetite. This research aims to see the strength of causal relationship between perception of the dish display and the appetite for dining. A descriptive approach is used through questionnaire to examine the magnitude of this relationship using simple linear regression. The results show that the clarity of the dish display impact strongly on visitors perception on dish display (R Square 87.81%). Then, perception on dish display gives strong impact on appetite (R Square 87%). This research concludes that neutral CCT preferences give higher impact on dining appetite since the perception on the dish display has previously evaluated positive